Historians on Chaucer : the 'general prologue' to the Canterbury tales - Rigby, S. H. (Stephen Henry), 1955-; Minnis, A. J. (Alastair J.) (Oxford, United Kingdom : Oxford University Press, 2014)
"As literary scholars have long insisted, an interdisciplinary approach is vital if modern readers are to make sense of works of medieval literature. In particular, rather than reading the works of medieval authors as addressing us across the centuries about some timeless or ahistorical 'human condition', critics from a wide range of theoretical approaches have in recent years shown how the work of poets such as Chaucer constituted engagements with the power relations and social inequalities of their time. Yet, perhaps surprisingly, medieval historians have played little part in this 'historical turn' in the study of medieval literature. The aim of this volume is to allow historians who are experts in the fields of economic, social, political, religious, and intellectual history the chance to interpret one of the most famous works of Middle English literature, Geoffrey Chaucer's 'General Prologue' to the Canterbury Tales, in its contemporary context. Rather than resorting to traditional historical attempts to see Chaucer's descriptions of the Canterbury pilgrims as immediate reflections of historical reality or as portraits of real-life people whom Chaucer knew, the contributors to this volume have sought to show what interpretive frameworks were available to Chaucer in order to make sense of reality and how he adapted his literary and ideological inheritance so as to engage with the controversies and conflicts of his own day. Beginning with a survey of recent debates about the social meaning of Chaucer's work, the volume then discusses each of the Canterbury pilgrims in turn. Historians on Chaucer should be of interest to all scholars and students of medieval culture whether they are specialists in literature or history"--
1. Reading Chaucer: Literature, History, and Ideology / Stephen H. Rigby -- 2. Chaucer the Poet and Chaucer the Pilgrim / Caroline M. Barron -- 3. The Knight / Stephen H. Rigby -- 4. The Squire / Craig Taylor -- 5. The Yeoman / Anthony J. Pollard -- 6. The Prioress and the Second Nun / Katherine J. Lewis -- 7. The Nun's Priest / Marilyn Oliva -- 8. The Monk / Martin Heale -- 9. The Friar / G. Geltner -- 10. The Merchant / Richard Goddard -- 11. The Clerk / Charles F. Briggs -- 12. The Sergeant of Law / Anthony Musson -- 13. The Franklin / Peter Coss -- 14. The Five Guildsmen / Gervase Rosser -- 15. The Cook / Christopher M. Woolgar -- 16. The Shipman / Wendy R. Childs -- 17. The Doctor of Physic / Carole Rawcliffe -- 18. The Wife of Bath / Ruth Mazo Karras -- 19. The Parson / David Lepine -- 20. The Ploughman / Mark Bailey -- 21. The Miller / Paul Freedman -- 22. The Manciple / Nigel Ramsay -- 23. The Reeve / David Stone -- 24. The Summoner / Ian Forrest -- 25. The Pardoner / Rosemary Horrox -- 26. The Host / Martha Carlin -- Conclusion: Historicism and its Limits / Stephen H. Rigby.
Includes bibliographical references and index.
Keywords: Chaucer, Geoffrey, -- -1400 -- Criticism and interpretation; Chaucer, Geoffrey, -- -1400.; England -- Intellectual life -- 1066-1485.; Great Britain -- History -- 14th century; England -- Social conditions -- 1066-1485.; England -- Social life and customs -- 1066-1485.; Chaucer, Geoffrey, -- -1400.; Intellectual life; Great Britain